Investigation of low-pressure ultraviolet radiation on inactivation of rhabitidae nematode from water. - Mohammad Hadi Dehghani; Gholam-Reza Jahed; Ahmad Zarei (Tehran University of Medical Sciences, 2013)
Rhabditidae is a family of free-living nematodes. Free living nematodes due to their active movement and resistance to chlorination, do not remove in conventional water treatment processes thus can be entered to distribution systems and cause adverse health effects. Ultraviolet radiation (UV) can be used as a method of inactivating for these organisms. This cross sectional study was done to investigate the efficiency of ultraviolet lamp in the inactivation of free living nematode in water.The effects of radation time, turbidity, pH and temperature were invistigated in this study. Ultraviolet lamp used in this study was a 11 W lamp and intensity of this lamp was 24 μw / cm(2).Radiation time required to achieve 100% efficiency for larvae nematode and adults was 9 and 10 minutes respectively. There was a significant correlation between the increase in radiation time, temperature rise and turbidity reduction with inactivation efficiency of lamp (P